Colorectal cancer treatment and survival over three decades at four major public hospitals in South Australia: trends by age and in the elderly. (3rd June 2016) - Roder, D.; Karapetis, C.S.; Wattchow, D.; Moore, J.; Singhal, N.; Joshi, R.; Keefe, D.; Fusco, K.; Powell, K.; Eckert, M.; Price, T.J.
Abstract : Data from registries at four major public hospitals in South Australia indicate increased 5‐year disease‐specific survivals for colorectal cancer from 48% to 63% between 1980–1986 and 2005–2010. For 80+ year olds, the increase was smaller, from 47% to 52%. Risk of case fatality halved overall, adjusting for age, gender, stage, differentiation and sub‐site. Patients aged 80+ years had a lower risk reduction of about a third (hazards ratio: 0.69; 95% confidence limits, 0.52–0.92). Percentages having surgery and other specified treatments were lower for 80+ year olds than younger cases, although increases in treatment intensity occurred in this age range during 1980–2010, as seen in younger ages, in accordance with guidelines. The study illustrates the important feedback clinical registries can provide to clinicians on care patterns and outcomes in their hospital settings. Feedback can be the subject of local deliberations on how to achieve the best outcomes, including in the elderly by considering the best trade‐offs between optimal cancer care and accommodations for co‐morbidity and frailty. Clinical registry data can be used in comparative effectiveness research in local settings where there are sufficient case numbers.